On the Streets: Deprivation, risk, and communities of care in pandemic times - Ruiz Muriel, Martha Cecilia (Anti-Trafficking Review, 2023)
Following the COVID-19 pandemic, public concerns about ‘vulnerable people in street situation’ have grown in South American countries. These concerns focus on the risk of sexual violence, exploitation, and human trafficking faced by migrants and women in the sex sector. This article examines these public concerns and the discourses of risk that structure them, taking Ecuador and the border province of El Oro as a case study. It analyses how irregularised migrants and women offering sexual and erotic services talk about ‘risk’ and ‘exploitation’, and how they respond to crisis, controls, and restrictions by becoming involved in risky activities and building communities of care. These communities are solidarity alliances that connect and offer mutual support to people confronting deprivation and violence. They are not restricted to the household or the domestic sphere; rather, they constitute different forms of ‘family’ and ‘home’ building. The article is based on a participatory research in El Oro, a place with a long history of human trafficking that has not been recognised or studied.